Eutrombicula daemoni Bassini-Silva and Jacinavicius, 2018 (Trombidiformes: Trombiculidae) parasitizing a dog in Brazil - Tortoriello Barbosa Sampaio, Rafaella (2020)
Chigger mites are ectoparasites of terrestrial vertebrates and can cause severe dermatitis in their hosts, known as trombiculiasis. There are 69 recognized species of chiggers in Brazil that parasitize most vertebrate taxa except domestic dogs. In this study, we report the first known record of trombiculiasis with a domestic dog as a host in Brazil. This record additionally represents a new locality record for Eutrombicula daemoni in the country.